(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Bauhinia, Testa surface pattern, Scanning electron microscopic studies Â DOI: 10.3329/bjpt.v15i2.1754 Â Bangladesh J. Plant Taxon. 15(2): 159-161, 2008 (December)